The Effect of Human Development Index Components on Economic Growth in Central Kalimantan Province - Nina Amelia (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2019)
This study analyzes how the partial and simultaneous influence of the components of the Human Development Index on Economic Growth. The method used in this research is descriptive-quantitative approach. The data used in this study is cross section data, namely all districts / cities in Central Kalimantan Province and time series data from 2010 to 2019. The collected data is then analyzed using panel data regression, the software used is Eviews version 10. The results of this study indicate that partially the Health Index has a negative and insignificant effect on Economic Growth. The Education Index partially has a positive and significant effect on Economic Growth. Purchasing Power Index (Expenditure) partially has a negative and significant effect on Economic Growth. As well as the overall Components of the Human Development Index; Health Index, Education Index and Purchasing Power Index (Expenditure) simultaneously affect Economic Growth